2009
DOI: 10.1002/jbm.a.32430
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescent PEG‐PCL micelles for imaging hydrogen peroxide

Abstract: Hydrogen peroxide is one of the fundamental molecules of biology, regulating key cell signaling pathways and the development of numerous inflammatory diseases. There is therefore great interest in developing contrast agents that can detect hydrogen peroxide in vitro and in vivo. In this report, we present a new contrast agent for imaging hydrogen peroxide, termed the chemiluminescent poly(ethylene glycol)-b-poly(e-caprolactone) (PEGPCL) micelles (CPMs), which can detect hydrogen peroxide at nanomolar concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 25 publications
1
28
0
2
Order By: Relevance
“…In this study, the molar ratio of cyclohexanedimethanol to HBA was decided after the careful consideration of stability in aqueous environments and reactivity to H 2 O 2 [6,16]. It has been reported that the aromatic peroxalate compounds instantaneously react with H 2 O 2 specifically to decompose into carbon dioxide, and rapidly degrade under aqueous conditions via hydrolysis [6,23,24]. In contrast, polyoxalate with aliphatic peroxalate ester has low reactivity to H 2 O 2 and undergo slow hydrolytic degradation under aqueous conditions.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, the molar ratio of cyclohexanedimethanol to HBA was decided after the careful consideration of stability in aqueous environments and reactivity to H 2 O 2 [6,16]. It has been reported that the aromatic peroxalate compounds instantaneously react with H 2 O 2 specifically to decompose into carbon dioxide, and rapidly degrade under aqueous conditions via hydrolysis [6,23,24]. In contrast, polyoxalate with aliphatic peroxalate ester has low reactivity to H 2 O 2 and undergo slow hydrolytic degradation under aqueous conditions.…”
Section: Discussionmentioning
confidence: 96%
“…However, a major barrier to POCL-based systems application is that peroxalate derivatives are not so stable and inclined to hydrolyze in aqueous or protic solvents [15]. Therefore, the protection of peroxalate esters from hydrolysis is the key factor to peroxalate NPs, for example, the formation of minisize organic reactor in aqueous systems through copolymer micelles [16] or microemulsions [17]. Meanwhile, with the peroxalate esters and the fluorescent dyes together in the same phase, the energy transfer is expected to be improved [18].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Dasari et al developed chemiluminescent micelles composed of polycaprolactone-co-polyethylene glycol (PCL-PEG) copolymer and diphenyl peroxalate which is more stable than bis(2,4,6-trichlorphenyl) oxalate in water. 16 Diphenyl peroxalate was encapsulated in the hydrophobic cores and thus protected from water hydrolysis. Diphenyl peroxalate has poor stability against water hydrolysis, but the encapsulation in the hydrophobic core of micelles increased its stability.…”
mentioning
confidence: 99%